Pengaruh Konsentrasi Katalis Dan Rasio Molar Umpan Terhadap Metanol Pada Pembuatan Biodiesel Dari CPO Menggunakan Reaktor membran - Leri Priadinanta; Syarfi Syarfi; Jecky Asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Biodiesel is an alkyl esters of long chain fatty acids derived from fatty material such as animal fat. A research synthesis of biodiesel from waste CPO(Crude Palm Oil) into biodiesel with a KOH catalyst. In this research review of physical properties (density, viscosity and acid number), analyzing the chemical content of biodiesel, the influence of the molar ratio of methanol to CPO(Crude Palm Oil) the percentage of conversion and optimal transesterification catalyst in the transesterification reaction in biodiesel synthesis. 300 grams of CPO(Crude Palm Oil), versus 1:14 methanol to oil molar, catalyst 1% of the weight of oil input into the biodiesel reactor and then the process of biodiesel synthesis performed on the operating conditions of 60 ° C temperature  for 150 minutes. The results showed that the optimum conversion catalyst with 1% methanol 1:14 molar ratio that is equal to 85,45%. Physical test results obtained by the density of 888 kg/m3, 5,94 cSt viscosity, acid number 0.707 mg-koh/gr sample. Results obtained have characteristics approaching the characteristics of biodiesel Indonesian National Standard (SNI). Kata kunci : CPO(Crude Palm oil), Biodiesel, transesterification, Conversion